Reactivation of the Spent Residue Fluid Catalytic Cracking (RFCC) Catalyst through Acid Treatment for Palm Oil Cracking to Biofuels - Rahma Amalia; Teguh Riyanto; Istadi Istadi (Diponegoro University, 2021)
This work discusses the treated spent Residue Fluid Catalytic Cracking (RFCC) catalysts using sulfuric or citric acids to examine the impact of acid treatment on the catalyst physicochemical properties and structural characteristics. The catalysts were characterized by X-ray diffraction (XRD), X-ray fluorescence (XRF), and Brunauer−Emmett−Teller-Barrett−Joyner−Halenda (BET-BJH) methods. The catalytsts were performed in a continuous fixed-bed reactor for catalytic cracking of palm oil. Changes of the catalyst characteristics and catalytic performance testing of the catalyst after the acid treatment for palm oil cracking process were discussed. It was found that the acid treatment on the spent RFCC catalyst can increase the surface area and pore volume of catalysts as well as the crystallinity. The closed pores in the spent RFCC are opened by acid treatment by eliminating heavy metals. Concerning to the catalytic performance, the acid-treated catalysts had better performance than the non-treated catalyst, which could increase selectivity of the kerosene-diesel range fraction from 47.89% to 55.41%. It was interested, since the non-treated catalyst could not produce gasoline fraction, while the acid-treated catalsysts could produce gasoline fraction at selectivity range of 0.57 – 0.84%. It was suggested that both sulfuric or citric acids treatment could increase the cracking performance of spent RFCC catalyst by shifting the product to lower hydrocarbons.